If something looks like an apple, is it necessarily an apple? Some considerations about so-called “statin-induced polymyalgia rheumatica” - Ciro Manzo (Rheumatology, 2019)
The existence of polymyalgia rheumatica (PMR) induced by statins has been hypothesised by some investigators. This review article highlights the fact that there is no evidence it is real. On the contrary, PMR and statin-associated muscle symptoms (SAMS) are two totally different conditions. Shoulder and hip ultrasound (US) examinations can make an important contribution in distinguishing a true case of PMR from a PMR-like illness induced by statins. The possibility that SAMS may worsen the clinical manifestations of a PMR patient should be taken into account in clinical practice, and drug discontinuation should be proposed when deterioration or relapse is not otherwise justifiable.